Aire-expressing ILC3-like cells in the lymph node display potent APC features - Yamano, Tomoyoshi; Dobeš, Jan; Vobořil, Matouš; Steinert, Madlen; Brabec, Tomáš; Ziętara, Natalia; Dobešová, Martina; Ohnmacht, Caspar; Laan, Martti; Peterson, Part; Benes, Vladimir; Sedláček, Radislav; et al. (The Journal of experimental medicine, 2019)
The autoimmune regulator (Aire) serves an essential function for T cell tolerance by promoting the "promiscuous" expression of tissue antigens in thymic epithelial cells. Aire is also detected in rare cells in peripheral lymphoid organs, but the identity of these cells is poorly understood. Here, we report that Aire protein-expressing cells in lymph nodes exhibit typical group 3 innate lymphoid cell (ILC3) characteristics such as lymphoid morphology, absence of "classical" hematopoietic lineage markers, and dependence on RORγt. Aire+ cells are more frequent among lineage-negative RORγt+ cells of peripheral lymph nodes as compared with mucosa-draining lymph nodes, display a unique Aire-dependent transcriptional signature, express high surface levels of MHCII and costimulatory molecules, and efficiently present an endogenously expressed model antigen to CD4+ T cells. These findings define a novel type of ILC3-like cells with potent APC features, suggesting that these cells serve a function in the control of T cell responses.
Keywords: Animals; přirozená imunita; Phenotype; lymfocyty; transkripční faktory; Histocompatibility Antigens Class II; Mice, Knockout; myši knockoutované; Transcription, Genetic; lymfatické uzliny; Antigen-Presenting Cells; Mice; Transcription Factors; antigeny CD11; Mice, Inbred BALB C; myši; jaderné receptory - podrodina 1, skupina F, člen 3; CD11 Antigens; regulace genové exprese; genetická transkripce; antigen prezentující buňky; myši inbrední BALB C; Immunity, Innate; Nuclear Receptor Subfamily 1, Group F, Member 3; Lymph Nodes; Lymphocytes; Epithelial Cell Adhesion Molecule; fenotyp; zvířata; Gene Expression Regulation; MHC antigeny II. třídy; adhezní molekula epiteliálních buněk